2000
DOI: 10.1034/j.1399-302x.2000.150603.x
|View full text |Cite
|
Sign up to set email alerts
|

Two distinct hemolysins in Trichomonas tenax ATCC 30207

Abstract: An oral protist Trichomonas tenax ATCC 30207 was investigated for the ability to lyse erythrocytes of sheep, rabbits, horses and humans. Five fractions, including intact cells, culture supernatant, culture filtrate, cell debris and lipid-enriched fractions, were prepared from the protozoan cells, and their hemolytic activities were assayed under various conditions. All the samples except culture supernatant had hemolytic activities, which were due to two different kinds of hemolysins. One hemolysin was protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…However, the presence of these potentially pathogenic microorganisms in the oral cavity was more prevalent in the gingivitis condition when compared to periodontitis. It has been demonstrated that T. tenax presents activity mediated by cysteine endopeptidases which hydrolyze collagen molecules types I, III, IV, V and also lyse human eritrocytes (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…However, the presence of these potentially pathogenic microorganisms in the oral cavity was more prevalent in the gingivitis condition when compared to periodontitis. It has been demonstrated that T. tenax presents activity mediated by cysteine endopeptidases which hydrolyze collagen molecules types I, III, IV, V and also lyse human eritrocytes (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…Authors have detected the capacity of T. tenax ATCC 30207 to adhere to diverse cells and induce cytotoxicity [17], while others studies showed no adherence or cytotoxic property [18][19]. Moreover, flagellates produce numerous enzymes, such as cysteine protease, cathepsin B like protein, haemolysins, metalloproteinase and other proteinases that could participate in the breakdown of collagen, gelatin observed in periodontal diseases [20][21][22][23][24][25]. Live trophozoites of the Hs-4 strain of T. tenax failed to induce secretion of IL-1β, IL-8, IL-10 or TNFα from macrophages.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…But Bózner et al concluded that it would be of interest to purify T. tenax enzymes and test their effect on extracellular matrix proteins in the oral cavity [25]. In addition to these enzymes, T. tenax seems to be able to produce haemolysins, which are also synthesised by many pathobionts such as P. gingivalis, Prevotella intermedia, A. actinomycetemcomitans and Treponema denticola [50][51][52][53]22].…”
Section: The Postulate "Virulence Factors"mentioning
confidence: 99%
“…Nagao i wsp. stwierdzili, że hemolizyny syntetyzowane przez ten gatunek są zdolne do lizy erytrocytów ludzkich, owczych, króliczych i końskich (73). Enzymy wytwarzane przez T. tenax oddziaływają destrukcyjnie na błonę śluzową jamy ustnej i tkanki przyzębia (47,59,62).…”
Section: Chorobotwórczość I Czynniki Zjadliwościunclassified